Demographics in the "Marriage Market" of the Sverdlovsk Region - Sinelnikov, Aleksandr Borisovich (Economy of Regions, 2017)
The article is devoted to the analysis of “marriage market” in the Sverdlovsk region and its comparison with the corresponding situation in the Russian Federation. In recent years, the level of marriage rate (per 1000 population) has reduced. According to the first hypothesis of the author, the decline in the marriage rate is a result of deterioration in the “marriage market”. This deterioration is due to the ageing of the population; disproportion between the number of unmarried men and women; unrealistic intentions of many men to marry women significantly younger than themselves (women rarely agree to a marriage with a large age difference). A second hypothesis is that the number of marriages decreases because people do not want to marry, even if there are potential brides and grooms age-appropriate for them. To test both hypotheses, the author applies his unique method of nuptial potentials. Under this method, the number of marriages is compared not with the number of population, nor with the number of unmarried men (or unmarried women). It is compared with additional nuptial potential that is with the maximum possible number of marriages in this situation in the marriage market. Calculations by the method of nuptial potential have confirmed both author’s hypotheses, and showed that the situation in “marriage market” is similar in the Sverdlovsk region and across Russia as a whole. Moreover, the method of nuptial potentials can be used to compare demographic projections taking into account the nuptiality.